EEG-BBNet: A Hybrid Framework for Brain Biometric Using Graph Connectivity - Lakhan, Payongkit; Banluesombatkul, Nannapas; Sricom, Natchaya; Sawangjai, Phattarapong; Sangnark, Soravitt; Yagi, Tohru; Wilaiprasitporn, Theerawit; Saengmolee, Wanumaidah; Limpiti, Tulaya (My University, 2025)
Most EEG-based biometrics rely on either convolutional neural networks (CNNs) or graph convolutional neural networks (GCNNs) for personal authentication, potentially overlooking the limitations of each approach. To address this, we propose EEG-BBNet, a hybrid network that combines CNNs and GCNNs. EEG-BBNet leverages CNN’s capability for automatic feature extraction and the GCNN’s ability to learn connectivity patterns between EEG electrodes through graph representation. We evaluate its performance against solely CNN-based and graph-based models across three brain–computer interface tasks, focusing on daily motor and sensory activities. The results show that while EEG-BBNet with Rho index functional connectivity metric outperforms graph-based models, it initially lags behind CNN-based models. However, with additional fine-tuning, EEG-BBNet surpasses CNN-based models, achieving a correct recognition rate of approximately 90%. This improvement enables EEG-BBNet to adapt its learning in new sessions and to acquire different domain knowledge across various BCI tasks (e.g., motor imagery to steady-state visually evoked potentials), demonstrating promise for practical authentication.
Keywords: (GCNN); brain biometrics; deep learning (DL); EEG; functional connectivity; graph convolutional neural network; Sensor applications